2011
DOI: 10.1186/1687-1847-2011-39
|View full text |Cite
|
Sign up to set email alerts
|

Infinitely many sign-changing solutions for a Schrö dinger equation

Abstract: We study a superlinear Schrödinger equation in the whole Euclidean space ℝ n . By using a suitable sign-changing critical point, we prove that the problem admits infinitely many sign-changing solutions, under weaker conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…For a more complex situation, we refer the reader to [14]. The related studies on the elliptic equations also can be found in [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…For a more complex situation, we refer the reader to [14]. The related studies on the elliptic equations also can be found in [15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…Obviously, we can prove that Φ satisfies condition (C) in the similar way as Lemma 2.3, and Φ(−u) = Φ(u) by using (F 5 ). Then, we only need to check conditions (A 1 ) and (A 2 ) of the fountain theorem (see [4,6,7,14,15,25]). …”
Section: Lemma 24 ([5 11])mentioning
confidence: 99%
“…Finally, by the generalized mountain pass theorem (see [11,14,17,18,27]), for a given k ∈ N, there exists a critical point…”
Section: Subharmonic Solutions Of Elliptic Equationmentioning
confidence: 99%
“…There is growing results about elliptic system, which comes from biological and physiological evidence, such as [1][2][3][4][5][6][7][8][9]. A more suitable general predator-prey model should be based on the so-called ratio-dependent theory, which asserts that the per capita predator growth rate should be a function of the ratio of prey to predator abundance.…”
Section: Introductionmentioning
confidence: 99%